2016
DOI: 10.4236/ojn.2016.63017
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the 8-Item Morisky Medication Adherence Scale in Chronically Ill Ambulatory Patients in Rural Greece

Abstract: Objective: To validate a Greek version of the structured self-reported 8-item Morisky Medication Adherence Scale (MMAS-8) and determine its psychometric properties in patients with chronic illnesses. Methods: A cross-sectional survey was conducted in a small public hospital and a public health care centre, in a rural town in western Greece. The sample consisted of 100 patients with various chronic illnesses. Data were collected between January-May 2011, on the Greek version of the MMAS-8 and Beliefs about Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 36 publications
0
23
0
4
Order By: Relevance
“…The questionnaire's first seven elements have yes/no answers, while the last element has 5 answers (Likert scale). The Moriski questionnaire has a sensitivity of 93% and a specificity of 53% , it has been validated in "low-income minority patients treated for high blood pressure who seek routine care in a clinic"; alsoit has been recently validated in Greece with the participation of D. Morisky [7]. In addition, MMAS-8 has been validated with remarkable validity and reliability in patients with other chronic diseases.…”
Section: Measurement Of Adherencementioning
confidence: 99%
“…The questionnaire's first seven elements have yes/no answers, while the last element has 5 answers (Likert scale). The Moriski questionnaire has a sensitivity of 93% and a specificity of 53% , it has been validated in "low-income minority patients treated for high blood pressure who seek routine care in a clinic"; alsoit has been recently validated in Greece with the participation of D. Morisky [7]. In addition, MMAS-8 has been validated with remarkable validity and reliability in patients with other chronic diseases.…”
Section: Measurement Of Adherencementioning
confidence: 99%
“…7 Yagiz uresin et al, conducted a double blind, multicenter trial on 837 patients with DM and HTN and conclude that Combination of aliskiren with ramipril provided great decrease in blood pressure. [11][12][13][14][15] According to a Review article performed by Anchala R et al, the overall prevalence for hypertension in India was 29.8%. [19][20][21][22] HTN is almost twice as frequent in patients with DM when compared with patients without disease.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] One of the most important issue in the effective treatment of Sub chronic and chronic illnesses is patient medication adherence to prescribed medications. [10][11][12] Adherence is the degree to which a person's behaviour coincides with medical advice. [13][14][15][16] Adherence to prescribed medicines is a way to improve one's health, but patients may or may not adhere to the prescriptions.…”
Section: Introductionmentioning
confidence: 99%
“…While the matrix component of this questionnaire were 4 factor components, with each component matrix value or factor loading > 0.5. This indicated that ten question items were valid for use in patients with DM-hypertension [18].…”
Section: Behavioural Level Questionnaire Validationmentioning
confidence: 94%
“…Further research is needed to develop this instrument through focus group discussions (FGD) to explore the understanding levels of patients. The percentage distribution of the respondents' answers to each question item are given in Table 4. Ten valid items were then tested for validity by factor analysis to see the correlation among fellow indicators simultaneously [18]. The Determinant of Correlation Matrix value is 0.001, this value approaches 0 thus the correlation matrix between the variables is interrelated.…”
Section: Behavioural Level Questionnaire Validationmentioning
confidence: 99%